Overcoming tight perihilar malignant biliary obstructions during percutaneous biliary intervention in Nigerian patients: case reports - Hammed A. Ninalowo; Peter T. Adenigba; Aderemi O. Oluyemi (The Egyptian Journal of Radiology and Nuclear Medicine, 2024)
Abstract Background A major challenge of either endoscopic or percutaneous approach to placing palliative biliary stents is the difficulty in traversing tight perihilar malignant obstructions. This can be overcome with a rendezvous approach (combined endoscopic retrograde cholangiopancreatography (ERCP)/percutaneous approach) or may require initial placement of an external drain and reattempting later. Interventional radiology for biliary obstruction is still in infant days in our locality. Herein, we describe two cases of perihilar malignant biliary obstruction (MBO) managed at a private facility in Lagos, Nigeria, in which we had to come up with a creative approach to crossing these tight junctions in the absence of ERCP facilities. This was done by securing percutaneous retrograde access into the common bile duct and combining it with the initially unsuccessful anterograde approach. In both cases, this combined percutaneous anterograde/retrograde approach resulted in successful traversal of the malignant obstruction and placement of internal biliary stents. Case presentation We present the case of two elderly patients with tight malignant biliary obstruction (MBO), one from a suspected cholangiocarcinoma and the other from hepatic metastatic colorectal carcinoma. Both patients had successful traversal of the obstruction via a combined percutaneous anterograde/retrograde approach and biliary stenting. Conclusions Our case reports demonstrate an unusual approach that should assist interventional radiologists in resource-limited setting who seek for a viable option to those presently available for traversing perihilar MBOs in the percutaneous placement of internal stents.